Macrophage immunometabolism during flavivirus infection - Donkoh, Jasmine, author; Rovnak, Joel, advisor; Quackenbush, Sandra, committee member; Foy, Brian, committee member; Perera, Rushika, committee member; Chen, Chaoping, committee member (Colorado State University. Libraries, 2022)
Dengue virus (DENV) and Zika virus (ZIKV) are mosquito borne flaviviruses that are transmitted by the Aedes spp. mosquito and have caused outbreaks in Africa, Asia, the south Pacific, and the Americas. Infection with DENV can cause severe illness, such as dengue hemorrhagic fever and dengue shock syndrome, while infection with ZIKV can result in congenital abnormalities, such as microcephaly, and spontaneous abortions. Although disease outcome for these viruses is markedly different, both DENV and ZIKV both target monocytes and macrophage for pathogenesis. Macrophage are among the first cells to be infected by DENV and ZIKV and are disseminated throughout the body. While macrophage are an important cell in flavivirus pathogenesis, the mechanisms by which viruses modulate macrophage function are not fully understood. In this dissertation, I present data that attempts to explain the interaction between macrophage and flaviviruses, as well as investigate the mechanisms in which DENV and ZIKV control macrophage gene expression and metabolism. The most widely used macrophage cell line, THP-1 cells, are cultured as immature monocytes. To become naïve macrophage, these cells are treated with phorbol 12-myristate- 13 acetate (PMA). Once THP-1 monocytes are differentiated into naïve macrophage, they can be polarized into different macrophage subsets. Even though THP-1 macrophage are widely used, the protocols in which to differentiate and polarize cells are not consistent. In chapter 2, we optimize methods to differentiate and polarize THP-1 cells. We measure gene expression and cellular metabolism during differentiation and polarization to characterize macrophage phenotype. These data, coupled with published literature, show that this model is a reliable system to study macrophage biology and flavivirus-macrophage interactions. We use the methods developed in this aim throughout the dissertation. Macrophage metabolism and phenotype determine immune function. Inflammatory (M1) macrophage are inflammatory and mount a strong anti-viral response, while anti-inflammatory (M2) macrophage dampen anti-viral responses. Viruses can alter macrophage phenotype for efficient replication and immune evasion. In chapter 3 we elucidated the role of macrophage polarization on DENV replication, showing that M1 macrophage have suppressed DENV replication while M2 macrophage support replication. In addition, we characterized the impact of DENV infection on M1 and M2 gene expression and metabolism. DENV infection resulted in an upregulation of inflammatory and anti-inflammatory genes in both M1 and M2 macrophage. Infection resulted in similar metabolic profiles in M1 and M2 cells, suggesting that DENV infection reprograms cellular metabolism in a way that is favorable for replication, regardless of macrophage phenotype. The key difference between M1 and M2 cells was the upregulation of interferon genes, where M1 mounted a strong interferon response, M2 mounted a subdued response. The difference in the interferon response could explain the difference in DENV replication observed in the two phenotypes. These data add to the ongoing literature on immunometabolism and its impact on viral pathogenesis. Cyclin dependent kinase 8 (CDK8) and CDK19 are transcriptional cofactors that regulate expression of inflammatory and anti-inflammatory genes. In addition, inhibition of CDK8/19 during DENV infection leads to decreased replication, as well as metabolic shifts in Huh7 cells, a liver cell line. In chapter 4, we investigate the role of CDK8/19 on viral replication and inflammatory/ anti- inflammatory gene expression. We found that inhibition of CDK8/19 kinase activity increased DENV replication and anti-inflammatory gene interleukin 10 (IL-10) expression. In contrast, inhibition of kinase activity decreased expression of inflammatory genes C-X-C motif chemokine ligand 10 (CXCL10). Furthermore, I found distinct mechanisms for each kinase through analysis of DENV-infected CDK8 and CDK19 knockdown cells. Knockdown of CDK8 mimics chemical inhibition of CDK8/19, while knockdown of CDK19 did not change expression in CXCL10 or IL-10. These data indicate that CDK8 and CDK19 regulate the transcription of different genes during DENV infection in macrophage. These data contribute the basic understanding of CDK8/19 regulation during viral infection. Macrophage phenotype plays a large role in ZIKV pathogenesis, where macrophage found near the placenta are an anti-inflammatory phenotype and are susceptible to infection. In chapter 5, we investigated the role of cyclin dependent kinase 8 and phenotype in Zika virus pathogenesis. We found CDK8 gene expression increase throughout infection, while CDK8 kinase inhibition decreased viral replication. Furthermore, inhibiting CDK8/19 kinase activity led to a decrease in CXCL10 and an increase in IL-10, as seen in a DENV model of infection. We also found that M2 macrophage were more susceptible to infection than M0 or M1. These data suggest that CDK8/19 kinase activity could be a pan-flavivirus mechanism to regulate host gene expression during infection.
Keywords: immunometabolism; dengue virus; macrophage